Ossification of caroticoclinoid ligament and its clinical importance in skull-based surgery - Das,Srijit (2007)
CONTEXT: The medial end of the posterior border of the sphenoid bone presents the anterior clinoid process (ACP), which is usually accessed for operations involving the clinoid space and the cavernous sinus. The ACP is often connected to the middle clinoid process (MCP) by a ligament known as the caroticoclinoid ligament (CCL), which may be ossified, forming the caroticoclinoid foramen (CCF). Variations in the ACP other than ossification are rare. The ossified CCL may have compressive effects on the internal carotid artery. Thus, anatomical and radiological knowledge of the ACP and the clinoid space is also important when operating on the internal carotid artery. Excision of the ACP may be required for many skull-based surgical procedures, and the presence of any anomalies such as ossified CCL may pose a problem for neurosurgeons. CASE REPORT: We observed the presence of ossified CCL in a skull bone. A detailed radiological study of the CCL and the CCF was conducted. Morphometric measurements were recorded and photographs were taken. The ACP was connected to the MCP and was converted into a CCF. Considering the fact that standard anatomy textbooks do not provide morphological descriptions and radiological evaluations of the CCL, the present study may be important for neurosurgeons operating in the region of the ACP.